(untitled) (Italian Journal of Public Health, 2006)
Background: in the frame of the aging trend of the Italian population, hip fractures are supposed to be one of the most critical problems to be faced from health care professionals, public health researchers and policy makers. Methods and Results: the objective of this study was to quantify hip fractures’ incidence and costs in comparison with a severe-perceived disease such as acute myocardial infarction (AMI) in a sample of 790.000 people living in Lecce area. To evaluate incidence of hip fractures and AMI, we utilized hospitalization database from Local Health Authorities Lecce/1 and Lecce/2. DRGs were used as indicators of direct costs; rehabilitation costs, social and indirect costs were not computed, but the latest available literature data suggest that they exceed the overall direct costs. Conclusion: consistently with national surveys, our results show that hip fractures have an incidence comparable to AMI and higher costs.